Application of circadian biology to behavioural and physiological assessments in mice - Benson, Lindsay Anne (2016)
Circadian rhythms are present in all living organisms; daily oscillations of biological process from the expression of a gene to the number of times that an animal displays a given behaviour. The light/dark cycle is the primary cue that entrains these rhythms and the suprachiasmatic nuclei, within the hypothalamus are the central pacemaker which synchronises peripheral body clocks. Mice are useful circadian biology models and two peripheral circadian outputs were studied, locomotor activity and the rhythm of body temperature in a common inbred strain, the C57BL/6 mouse.